Nitrogen management and nitrous oxide emission from agriculture: Implication for climate change - Mohammed Wajid, I; Sathiya Bama, K; Meena, S; Kathirvelan, P; Prabu, P C (Plant Science Today, 2025)
Nitrous oxide (N₂O) is a potent greenhouse gas with a global warming potential approximately 298 times that of carbon dioxide over a 100-year period. Agriculture is a major contributor to global N₂O emissions, primarily using nitrogen (N) fertilizers and associated soil microbial processes such as nitrification and denitrification. This review synthesizes current knowledge on the mechanisms of N₂O production, the influence of soil physical, chemical and biological properties and the impact of nitrogen management practices on emission dynamics. It explores the effects of fertilizer types, application rates, timing and placement on N₂O fluxes, alongside emerging technologies such as enhanced-efficiency fertilizers and nitrification inhibitors. The review also highlights mitigation strategies including conservation tillage, optimized irrigation, crop rotations and integrated nutrient management. Understanding the complex interplay between agronomic practices and N₂O emissions is essential for designing climate-smart agriculture that sustains productivity while minimizing environmental impacts. Hence this paper focus on role of nitrogen mitigation on nitrous oxide emission and implication for climate change.